2020
DOI: 10.1158/1078-0432.ccr-20-0219
|View full text |Cite
|
Sign up to set email alerts
|

A Biomarker-enriched, Randomized Phase II Trial of Adavosertib (AZD1775) Plus Paclitaxel and Carboplatin for Women with Platinum-sensitive TP53-mutant Ovarian Cancer

Abstract: Preclinical studies show that adavosertib, a WEE1 kinase inhibitor, sensitizes TP53-mutant cells to chemotherapy. We hypothesized that adavosertib, plus chemotherapy, would enhance efficacy versus placebo in TP53-mutated ovarian cancer.Patients and Methods: Following safety run-in, this double-blind phase II trial (NCT01357161) randomized women with TP53-mutated, platinum-sensitive ovarian cancer to oral adavosertib (225 mg twice daily for 2.5 days/21-day cycle) or placebo, plus carboplatin (AUC5) and paclitax… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 43 publications
(55 reference statements)
0
62
0
Order By: Relevance
“…AZD1775 has also been shown to be tolerable when combined with irinotecan in pediatric solid refractory tumors ( 31 ). In a recent phase II study, the addition of AZD1775 to carboplatin enhanced median progression free survival in patients with p53 mutant ovarian cancer ( 34 ). Consistently, biopsy and blood samples collected in these studies have reported decreased phospho-CDC2 activity and increased γH2AX activity after AZD1775 combination therapy.…”
Section: Discussionmentioning
confidence: 99%
“…AZD1775 has also been shown to be tolerable when combined with irinotecan in pediatric solid refractory tumors ( 31 ). In a recent phase II study, the addition of AZD1775 to carboplatin enhanced median progression free survival in patients with p53 mutant ovarian cancer ( 34 ). Consistently, biopsy and blood samples collected in these studies have reported decreased phospho-CDC2 activity and increased γH2AX activity after AZD1775 combination therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Cell-cycle modulation has been pursued for OC treatment, as cell-cycle control mechanisms represent a critical component clinical outlook of the DNA-damage response, able to effectively detect DNA damage and halt cellular replication in order to initiate repair. Adavosertib (AZD1775), which inhibits the nuclear kinase WEE1, has emerged as a promising compound that is able to regulate G 2 -M transition and sensitize tumor suppressor p53-mutant cells to chemotherapy 7 . This year, the results of a double-blind phase 2 trial (NCT01357161) were reported in which 141 women with recurrent platinum-sensitive OC in which TP53 is mutated were randomized to receive oral adavosertib or placebo, in addition to chemotherapy 7 .…”
Section: Phase 1/2 Clinical Trialsmentioning
confidence: 99%
“…Adavosertib (AZD1775), which inhibits the nuclear kinase WEE1, has emerged as a promising compound that is able to regulate G 2 -M transition and sensitize tumor suppressor p53-mutant cells to chemotherapy 7 . This year, the results of a double-blind phase 2 trial (NCT01357161) were reported in which 141 women with recurrent platinum-sensitive OC in which TP53 is mutated were randomized to receive oral adavosertib or placebo, in addition to chemotherapy 7 . The addition of adavosertib improved progression-free survival (PFS) according to the enhanced RECIST 1.1 guidelines (ePFS; hazard ratio (HR), 0.63; 95% confidence interval (CI) 0.38-1.06; two-sided P = 0.080), meeting the predefined significance threshold (P < 0.2) 7 .…”
Section: Phase 1/2 Clinical Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the drugs targeting the DDR pathway, AZD1775 (MK-1775, adavosertib), an inhibitor of the tyrosine kinase WEE1, has shown efficacy in sensitizing many cancer types to DNA damaging agents in both preclinical studies and phase I/II clinical trials [29][30][31][32][33][34]. WEE1 is a crucial activator of the G2/M checkpoint, which stalls the cell cycle in response to DNA damage, by phosphorylating and inhibiting cyclin-dependent kinase 1/2 (CDK1/CDK2).…”
Section: Introductionmentioning
confidence: 99%